2012
DOI: 10.4028/www.scientific.net/kem.523-524.1080
|View full text |Cite
|
Sign up to set email alerts
|

Surface Nitriding of Al-Mg Alloys Using a Rotary Barrel Tank

Abstract: The authors developed a new nitriding process to form an aluminum nitride film on a pure aluminum surface. In this study, a rotary barrel polishing method was applied to gas nitriding in an attempt to form an aluminum nitride film on the surface of Al-Mg alloys. Nitriding was carried out at 823 K, 853 K, and 873 K for 3.6 ks to 25.2 ks. Alumina- and aluminum - 50mass% magnesium powders were used as the media that flowed in the barrel tank. An aluminum nitride film was formed on the aluminum alloy surfaces with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In a previous report, nitriding was conducted using Al-50 mass% Mg in activation powders. 7) The result in Fig. 7 denoted the same tendency as the previous results, and the film was considered to be adhered to the top of the substrate surface.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In a previous report, nitriding was conducted using Al-50 mass% Mg in activation powders. 7) The result in Fig. 7 denoted the same tendency as the previous results, and the film was considered to be adhered to the top of the substrate surface.…”
Section: Resultssupporting
confidence: 60%
“…A barrel tank was used for surface nitriding of aluminum substrates. Details of the nitriding system have been reported previously 6,7) . The barrel tank used in this study was octagonal, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A barrel tank, as shown in Figure 2, was used to nitride the surfaces of aluminum substrates. Details of the nitriding system have been reported previously 10,11) . An octagonal barrel tank was used in this study.…”
Section: Methodsmentioning
confidence: 99%